Psychology : - Lahey, Benjamin B. (McGraw-Hill, 2004)
The book offers useful knowledge on psychology. All psychological subjects are discussed throughout 7 parts: Introduction and foundations of psychology, Awareness, Learning and cognition, developmental psychology, The self, Health and adjustment and Social context